Creating rich information environmentt at the University of Zagreb - Vrana, Radovan (2010)
The Internet has caused significant changes to process of learning. The Web has become the most important information environment which supports different kinds of activities at universities, including research and teaching. To fulfill their mission of being institutions where excellence is expected in both of these two activities, universities must provide access to digital content and support its long-term preservation. Academic libraries help universities in realization of these two tasks by offering their holdings and services to researchers, teachers and students. By doing that, libraries support development of e-learning. This paper will present results from research in academic libraries at the University of Zagreb regarding opinions and attitudes of library heads about digital information resources and digital content, and their use in teaching and research.
Projekt MZOS
ENG